FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJAKEUANGAN PEMERINTAH DESA PASCA PENERAPAN UNDANG- UNDANG NOMOR 6 TAHUN 2014 - Retno Astuti Dewi; Wita Ramadhanti; Adi Wiratno (Jurnal Akuntansi Aktual, 2016)
Abstract:This research is quantitative research in the village government in the Banyumas Regency.The purpose of this research is to examine the effect of the planning, implementation village account-ing, fixed income, and internal control on the financial performance of village government. Thesampling method used in this study is a purposive sampling. The samples of this research are thevillages that have sent Village Budget Accountability Report of 2015 and fill out the questionnaire infull. The number of samples are 78 villages. Based on the results of research and analysis using the PLSand SPSS show that: (1) Planning does not positively affect the financial performance of VillageGovernment, (2) Implementation of accounting village has positive effect on the the financial perfor-mance of Village Government, (3) Fixed Income does not positively affect the financial performance ofVillage Government, (4) internal control negatively affects the financial performance of Village Gov-ernment, and (5) Implementation of accounting village has not been fully implemented in accordancewith the Regulation of the Minister of Internal Affairs No. 113 of 2014.Keywords: Planning, Implementation of Village Accounting, Fixed Income, and Internal Control, TheFinancial Performance of Village Government, After Implementation Law No. 6 of 2014